Paulo Freire's contributions to critical pedagogy - Gadotti, Moacir (2011)
Los contributions of Paulo Freire pedagogy críticaPaulo a la Freire disliked label pedagogies, but since introducedthe thesis that there is an education aspractice of domestication and educationthe practice of freedom, we can saythat there is a dogmatic teaching, forTherefore, domesticating and dialectical pedagogy, critical questioning. PaulFreire was a critic of the education of theirtime. His "pedagogy of the oppressed" is part of the great movement of "pedagogycritical ", also called" radical "or"Revolutionary", dependedo context